Global functional performance and caregiver assistance in children with pervasive development disorders - Patel, Shreya V.; Diwan, Shraddha; Shah, Nehal (International Journal of Contemporary Pediatrics, 2017)
Background: Pervasive developmental disorder (PDD) affects motor, social and communication function of a child which may lead to affection of global function. Pediatric Evaluation of Disability Inventory (PEDI) is used to assess performances, degree of functional limitations as well as the extent of caregiver assistance. Hence, the need of the study was to quantify the functionality and dependence level in children with PDD. The aim of the study was to quantify the overall functional performance and need for caregiver assistance in PDD. Methods: An observational study was carried out on 12 children (age 6 months - 7.5 years) diagnosed as PDD, taking rehabilitation at pediatric rehab department of SBB college of physiotherapy. After taking consent of primary caregiver PEDI questionnaire was administered by interview method. Demographic details were noted by physiotherapist. Results: The score of functional skills in three domains were self-care (mean 8.58±5.265), mobility (mean 15.58±15.300) and social function (mean 5.42±4.641). The score of caregiver assistance in three domains were self-care (mean 2.75±3.441), mobility (mean 8.83±11.907) and social function (mean 1.50±2.316). Among six domains 12 children had the lowest score in terms of social function for both caregiver assistance and functional skills. Conclusions: Present study concludes that social function is majorly affected in terms of caregiver assistance in children with PDD.